2021
DOI: 10.1097/pts.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

Reason for Exam Imaging Reporting and Data System: Consensus Reached on Quality Assessment of Radiology Requisitions

Abstract: The aim of this study was to reach consensus on quality assessment of clinical information in imaging requisitions using Reason for exam Imaging Reporting and Data System (RI-RADS).Methods: A Delphi study was conducted in September 2018 with a panel of 87 radiologists with diverse levels of experience from various settings (community hospitals, private hospitals, university hospitals, and clinics), of which 74.7% completed the survey. The agreement was assessed in the following subjects: (a) presumed effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Nevertheless, our results resonate with previous literature that generally reported poor imaging requests to be common [6][7][8][9][10][11][12]. They are also in line with the results of a recent survey in which the majority of radiologists (56.3 %) indicated that they encounter requisitions with incomplete or inaccurate data that make the interpretation challenging in more than half of the time [5]. Comprehensive studies on the determinants of poor quality imaging requests have also been lacking so far.…”
Section: Imaging Modalitysupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, our results resonate with previous literature that generally reported poor imaging requests to be common [6][7][8][9][10][11][12]. They are also in line with the results of a recent survey in which the majority of radiologists (56.3 %) indicated that they encounter requisitions with incomplete or inaccurate data that make the interpretation challenging in more than half of the time [5]. Comprehensive studies on the determinants of poor quality imaging requests have also been lacking so far.…”
Section: Imaging Modalitysupporting
confidence: 91%
“…However, even for seemingly routine procedures, it is crucial that referring physicians provide an adequate impression, clinical information, and diagnostic question to the imaging request, because the lack of this information has been recognized as a source of diagnostic errors [13]. In a recent survey among radiologists (the majority from the United States) 12.6 % indicated to have experienced at least one lawsuit potentially preventable with sufficient information in the imaging request [5]. In addition, if a radiologist frequently has to look up the missing information in the medical records or by contacting the requesting physician, this will slow down workflow and it might be a source of stress and frustration that may even refrain the radiologist from doing so in a busy practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structured reporting systems simplify the interpretation and reporting of imaging examinations, serve as a framework for consistent generation of recommendations, and improve the quality of patient care [12][13][14][15][16]. Our systematic review of the CT manifestations of COVID-19 showed a substantial inconsistency in description of imaging findings across the growing number of published studies [17].…”
Section: Role Of Chest Ct and Its Relationship With Rt-pcrmentioning
confidence: 93%